The Use of Remote Sensing and GIS in Studying the Dynamics of Irrigated Space in Guercif Plain (Morocco) - El hani, Lamfaddal; Bouberria, Abdelouahed (Iraqi Journal of Science, 2023)
The use of remote sensing and Geographic Information System (GIS) are among the most efficient modern tools to study the varied natural resources in terms of localization, identification of characteristics, and the study of its dynamics. Thus, the aim of this study is to show the importance of remote sensing and Geographical Information System in studying the Guercif irrigated plain. We will first process and analyze satellite images using the program (Erdas IMAGINE 15. 00) and then create thematic maps illustrating the irrigated area’s evolution (ArcGIS 10.8). The results revealed that since the late 20th century, the area of Guercif Plain has expanded significantly, with the total irrigated space that has been doubled many times by 2021. Significant landscape transformations accompanied this evolution, for Guercif Plain has turned from a barren and dry to a green agricultural space.